Role of Hsp100/Clp Protease Complexes in Controlling the Regulation of Motility in Bacillus subtilis - Molière, Noël; Hoßmann, Jörn; Schäfer, Heinrich; Turgay, Kürşad (Frontiers in Microbiology, 2016)
The Hsp100/Clp protease complexes of Bacillus subtilis ClpXP and ClpCP are involved in the control of many interconnected developmental and stress response regulatory networks, including competence, redox stress response and motility. Here we analyzed the role of regulatory proteolysis by ClpXP and ClpCP in motility development. We have demonstrated that ClpXP acts on the regulation of motility by controlling the levels of the oxidative and heat stress regulator Spx. We obtained evidence that upon oxidative stress Spx not only induces the thiol stress response, but also transiently represses the transcription of flagellar genes. Furthermore, we observed that in addition to the known impact of ClpCP via the ComK/FlgM-dependent pathway, ClpCP also affects flagellar gene expression via modulating the activity and levels of the global regulator DegU-P. This adds another layer to the intricate involvement of Clp mediated regulatory proteolysis in different gene expression programs, which may allow to integrate and coordinate different signals for a better–adjusted response to the changing environment of B. subtilis cells.